Towards a circular economy with application of salmon silage to a grassland in Chilean Patagonia - Zamora, Daniel; Radic Schilling, Sergio Javier (My University, 2025)
This study assessed the effects of salmon silage application on soil characteristics and vegetative production in three different trials. Carried out experiments in three different assays, soil incubation, pot experiment and field experiment, where measured parameters were soil pH, dry matter production, plant height, root density, nodules number in legumes, depending each experiment. The results shown in the soil incubation trial, soil pH decreased as the silage concentration incorporated into the soil increased. The greenhouse trial evaluated the growth responses of common forage species to silage application. Orchard grass (Dactylis glomerata) displayed the highest rate of biomass production (7.31 g/pot). In the field trial, biomass production was higher when silage was applied at a rate of 24 tons of silage per hectare plus 2 tons of lime compared to dry matter production in the control treatment and with traditional fertilizer rates. It is not recommended to use doses equal to or greater than 96 tons per hectare of silage as this resulted in reduced forage production or quality.
Keywords: patagonian region; rangeland; organic amendment; aquaculture; circular economy